Risk Management Practices in Green Building Projects - Tan, Chuan Soon (2021)
Green building projects utilize green construction methods, green materials and energy-efficient operational systems. Risk management in green building projects is a process used to recognize, analyse, treat and monitor risks by prioritizing the sustainability issues – social, economic and environment. Nowadays, incidence on project cost overrun in green building projects is increasing due to the complex green certification process and limited availability of green products in Malaysia. This study aims to propose a risk management model for green building projects through exploration of risk management in green building projects and evaluating best risk management practices adopted by green building project developers. Quantitative research methodology was adopted in this study through the use of questionnaire survey on green building project developer organizations in Malaysia. A total of 192 respondents were obtained and analysed. The findings show that developers tend to identify, analyse and evaluate risks in green building projects by conducting consultation or interviews with professionals and local agencies. It is found that risk transfer through contracts and government financial incentives are favoured by developers in mitigating project risks. Risks in green building projects are monitored and controlled by cooperatively performing Design Assessment (DA) with Green Building Index authority. Outcome of this study proves that risk management practices positively affect the green building project performance. A risk management model for green building projects is established to provide general guidance to green building project developers on best risk management practices that would help enhance project performance in terms of cost, quality and time.